Interpretacyjna zmiana Konstytucji V Republiki Francuskiej w zakresie zasady laickości .......... 15 - Deptalski, Mikołaj (Współczesne zmiany konstytucji w wybranych państwach europejskich: Pomiędzy partykularyzmem prawnym a wspólnotą doświadczeń, 2025)
INTERPRETATIVE AMENDMENT TO THE CONSTITUTION OF THE FIFTH FRENCH REPUBLIC REGARDING THE PRINCIPLE OF SECULARISMThe aim of this article is to present a theoretical concept of the interpretive constitutional amendment. This concept is presented and analyzed in the context of the amendment of the Constitution of the Fifth French Republic concerning the principle of laïcité, using the wearing of religious symbols in the public sphere as an example. The main research question is whether an interpretive constitutional amendment has occurred in the Constitution of the Fifth French Republic with regard to the principle of laïcité. To analyze and address this question, Section Two outlines the theoretical framework of the concept of interpretive constitutional amendment, its background in the open structure of law, and the characteristics of constitutional concepts. Section Three provides a historical overview of the principle of secularism in the context of French law, including the legal opinion issued by the Council of State in 1989. Section Four applies the concept of interpretive constitutional amendment to the French legislation after 2004, highlighting the shift in the understanding of the principle of laïcité. The article concludes with findings and reflections resulting from the conducted analysis.